Repeating patterns of virioplankton production within an estuarine ecosystem - Winget, Danielle M. (National Academy of Sciences, 2011)
The Chesapeake Bay, a seasonally variable temperate estuary, provides a natural laboratory for examining the fluctuations and impacts of viral lysis on aquatic microorganisms. Viral abundance (VA) and viral production (VP) were monitored in the Chesapeake Bay over 4 1/2 annual cycles, producing a unique, long-term, interannual study of virioplankton production. High and dynamic VP rates, averaging 7.9 × 10(6) viruses per mL per h, indicate that viral lysis impacts a significant fraction of microorganisms in the Chesapeake. Viral-mediated bacterial mortality, VA, VP, and organic carbon release all displayed similar interannual and seasonal trends with higher values in 2003 and 2006 than in 2004 and 2005 and peaks in early spring and summer. Surprisingly, higher rates of viral lysis occurred in winter, resulting in a magnified effect of viral lysis on bacterioplankton during times of reduced productivity. Viral lysis directly impacted the organic carbon pool, contributing on average 76 μg of C per L per d, an amount capable of sustaining ∼55% of Chesapeake Bay bacterial production. The observed repeating interannual patterns of VP and lysis are likely interlinked with seasonal cycles of host abundance and diversity, which are in turn driven by annual cycles in environmental conditions, emphasizing the complex interplay of seasonality and microbial ecology in the Chesapeake Bay.